Penanaman Pemahaman Seks Pranikah Bagi Siswa Melalui Layanan Informasi di Sekolah Menengah Kejuruan Telkom Pekanbaru - Fitra Herlinda (Educational Guidance and Counseling Development Journal, 2018)
This research aimed at knowing whether there was aninfluence of joining Informational Service on Personal Guidance toward student pre-marriage sex comprehension.  It was a Correlation that the subjects of this research were the eleventh-grade students of Accounting and Hospitality Department.  The object was theinfluence of joining Informational Service on Personal Guidance toward student pre-marriage sex comprehension.  The population of this research was all students of Accounting and Hospitality Department amount 116 students.  Considering the large number of population, Purposive sampling technique was used.  It was obtained 35 students as samples.  The technique of analyzing the data was Simple linear regression formula.  Based on the research findings, it could be known thatrobserved was 0.988 with 0.000 probability level.  It was obtained that robserved was higher than rtable at 5% and 1% significant levels (0.3338<0.988>0.4296).  Based on the testing, it could be concluded that Ha was accepted, and Ho was rejected.  It meant that there was a significantinfluence of joining Informational Service on Personal Guidance toward student pre-marriage sex comprehensionatTelecomVocational High School Pekanbaru.